Comparative role of intravitreal ranibizumab versus bevacizumab in choroidal neovascular membrane in age-related macular degeneration - Partha Biswas; Subhrangshu Sengupta; Ruby Choudhary; Subhankar Home; Ajoy Paul; Sourav Sinha (Indian Journal of Ophthalmology, 2011)
Context: Ranibizumab and bevacizumab are used widely for treating patients with choroidal neovascular membrane (CNVM) secondary to age-related macular degeneration (AMD). Aims: To determine and compare the efficacy and safety of intravitreal ranibizumab and bevacizumab in treatment of CNVM due to AMD. Settings and Design: Prospective comparative case series carried out in an eye institute and eye department of a hospital in Kolkata, India. Materials and Methods: One hundred and four eyes with CNVM due to AMD were randomized into two groups. Group A (n=54; 24 occult) received monthly intravitreal ranibizumab injections (0.5 mg in 0.05 ml) and Group B (n=50; 22 occult) received monthly bevacizumab injections (1.25 mg in 0.05 ml) for 3 consecutive months and then as per study criteria. Data analysis done using SPSS software. P-value of <0.05 was considered statistically significant. Results: The mean best corrected visual acuity (BCVA) in the ranibizumab group increased from 58.19 Early Treatment Diabetic Retinopathy Study (ETDRS) letters at baseline to 64 ETDRS letters at month 3 (P<0.001). In bevacizumab group mean BCVA increased from 56.80 to 61.72 ETDRS letters at month 3 (P<0.001). At the end of 18 months, there was no statistically significant difference between groups A and B with respect to change in BCVA (P=0.563) or central macular thickness (CMT; P=0.281), as measured by optical coherence tomography (Stratus OCT 3000). No significant sight-threatening complications developed. Conclusions: Ranibizumab and bevacizumab are equally safe and efficacious in treating CNVM due to AMD.